Effect of pore solution alkalinity on alkali–silica reaction (ASR) in metakaolin-based geopolymer - Lei, Jiawei (2025)
Geopolymer concretes have shown better resistance against alkali–silica reaction (ASR) than ordinary Portland cement concretes, which was attributed to the low pore solution alkalinity of the geopolymer. However, the alkalinity of the geopolymer pore solution depends on the concentration and volume of the activating solutions used and age of the geopolymer. The main objective of this study was to investigate the effects of pore solution alkalinity on the ASR expansion of the metakaolin-based geopolymer concrete. The chemistry of the pore solution of metakaolin-based geopolymer was studied, and its reaction with reactive and non-reactive aggregates was investigated. The concrete prism expansion tests showed no ASR-induced expansion in geopolymer despite sufficient pore solution alkalinity to attack the reactive aggregates. The SEM and XRD characterizations confirmed that no ASR-related gel was formed during the reaction between reactive aggregates and extracted pore solution. The chemical structure of the reaction product between aggregates and pore solution was characterized using MAS NMR and revealed no difference in the reaction products with reactive and non-reactive aggregates. The results suggest that the pore solution alkalinity is not the sole governing parameter for ASR expansion in the geopolymer.